Success determinants of small and medium enterprises: The case of Portugal - Portela, S. (ABSRC 2014 MILAN Conference Proceedings, 2014)
The success determinants of Portuguese small and medium enterprises (SMEs) are examined using a sample of 207 Portuguese firms from several industries listed in the Dun & Bradstreet database that are at least five years old and with ten or more employees. The empirical study is based on the Lussier (1995) success versus failure prediction model. Our results do not fully support the international research on the determinants of SMEs’ success. The determinants of Portuguese SMEs’ success are: capital, record-keeping and financial control, planning, professional advice, age of owner, and marketing skills. Using logistic regression, the model adequately fits the data, and accurately predicts 43.4 percent of the failed businesses and 87.0 percent of the successful businesses for an overall accuracy rate of 73.2 percent.